2007
DOI: 10.1589/jpts.19.33
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Findings during Recovery after Experimental Stroke in Monkeys-Assessment with Modified Hand Performance Test-

Abstract: Abstract. It is still unclear how rehabilitative intervention assists recovery from strokes. In order to address this question, we made an animal model to examine the recovery process after experimental strokes. The forelimb movements in 2 monkeys retrieving food from a well were analyzed with a videotape recording. A small infarction by coagulation of blood vessels was made in the forelimb areas after mapping of the primary motor areas. The recovery process was evaluated by measuring the time required for tak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
(35 reference statements)
2
2
0
Order By: Relevance
“…The first explanation proposes that the high number of trials performed in the modified Klu¨ver board task has increased the probability that subtle changes may still be statistically significant. The second explanation is consistent with the negative effect associated with the increase of well depth on the recovery of precision grip following injury (Fukushima et al, 2007), as the wells of the modified Klu¨ver board are deeper than the wells of the modified Brinkman board.…”
Section: Behavioral Resultssupporting
confidence: 64%
“…The first explanation proposes that the high number of trials performed in the modified Klu¨ver board task has increased the probability that subtle changes may still be statistically significant. The second explanation is consistent with the negative effect associated with the increase of well depth on the recovery of precision grip following injury (Fukushima et al, 2007), as the wells of the modified Klu¨ver board are deeper than the wells of the modified Brinkman board.…”
Section: Behavioral Resultssupporting
confidence: 64%
“…It is likely though that their well dimensions were more different than those used in the current study and therefore represent a greater degree of difficulty. This is supported by data from Fukushima et al (2007) that reported increasing latencies for retrieval of a food reward from wells of increasing depths in young animals. This study demonstrates that animals require 0.67 ± 0.27 s to retrieve a food reward from a well of 30 mm diameter and 10 mm depth but 2.16 ± 1.68 s to retrieve a food reward from a well of 30 mm diameter and 50 mm depth.…”
Section: Discussionsupporting
confidence: 61%
“…Observations of behavioral recovery might be important for future studies. The animals showed various CMPs 7 ) . For recovery, CMPs as abnormal patterns in acute hemiparesis should be suppressed 6 ) .…”
Section: Discussionmentioning
confidence: 97%